ANALYZING COMPETITIVE ADVANTAGES OF COMPANIES OF MINING AND CHEMICAL INDUSTRY IN RUSSIA - Anjelica L. Gendon (Вестник Российского экономического университета имени Г. В. Плеханова)
The article describes the key strategic lines in the development of the biggest Russian mining and chemical holding companies. The author explains the necessity to strengthen positions of Russian mining and chemical companies on global markets. It is shown that current changes on world and national commodity markets, main trends of present development of industry and world economy in general, such as globalization, consolidation of industries, extension and integration of enterprises, intensification of competition create unprecedented challenges and opportunities of developing industrial sector, in particular mining and chemical complex. New situation in economy causes the necessity to find and ground new variants of strategic competitive behaviour, as well as strategic planning of competitive advantages for their development and retaining. The author analyzes advantages of Russian mining and chemical companies, which can ensure success for Russian producers.